Pre-Service Teachers' Experience at Teaching Practicum - Wakhid Nashruddin (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2015)
For many years, the teaching and learning English (as a foreign language) in Indonesia has been considered unfruitful for students’ low ability in using the language in communication. For many times, government (as the leader of schools) and campus (as teacher producer) do not sit together to discuss this problem. This results to gaps between school and campus. I am interested in seeing this problem by viewing gaps occur in the process of campus preparing qualified English teachers. This paper will tell the result of my interviews with pre-service teachers about their experiences at teaching practicum program.